2021
DOI: 10.1590/1678-4324-2021190730
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Antiradical Properties of Pyroligneous Acid from a Preserved Bamboo, Guadua angustifolia Kunth

Abstract: Pyroligneous acid (PA) was obtained by condensation of the vapors produced in the thermal decomposition of culms residues from Guadua angustifolia Kunth (G. angustifolia) cultivated in Colombia, with and without previous preservation treatment with borax salts. Chemical characterization by GC-MS showed that PA extracts has high content of phenolic compounds. Mequinol, isocreosol, 4-ethylphenol, 4ethyl-2-methoxyphenol, 3,5-dimethoxy-4-hydroxytoluene and 2,6-dimethoxyphenol were the most abundant substances, ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…The application of PHWE at temperatures higher than 140 °C resulted in higher extraction yields and total phenolic contents than conventional extraction methods. The highest TPC value obtained in this work (7.6 mg GAE/g of plant material at 180 °C) was lower than the values for five native Brazilian bamboo species reported by Wroblewska et al (43.64~87.81 mg GAE/g RM) [ 46 ] but higher than the values from bamboo culms and related products reported by Gomez et al (1.59~3.84 mg GAE/g RM) [ 47 ], Gong et al (4.21 mg GAE/g RM) [ 48 ], and Nuzul et al (0.45~0.72 mg GAE/g RM) [ 33 ]. The literature data listed above (converted to the same unit) were all obtained from conventional extraction methods using organic solvents and measured by the FC method.…”
Section: Resultscontrasting
confidence: 73%
“…The application of PHWE at temperatures higher than 140 °C resulted in higher extraction yields and total phenolic contents than conventional extraction methods. The highest TPC value obtained in this work (7.6 mg GAE/g of plant material at 180 °C) was lower than the values for five native Brazilian bamboo species reported by Wroblewska et al (43.64~87.81 mg GAE/g RM) [ 46 ] but higher than the values from bamboo culms and related products reported by Gomez et al (1.59~3.84 mg GAE/g RM) [ 47 ], Gong et al (4.21 mg GAE/g RM) [ 48 ], and Nuzul et al (0.45~0.72 mg GAE/g RM) [ 33 ]. The literature data listed above (converted to the same unit) were all obtained from conventional extraction methods using organic solvents and measured by the FC method.…”
Section: Resultscontrasting
confidence: 73%
“…WD is rich in antioxidants, such as polyphenols [15,17,37], and is effectively used to increase both the chlorophyll content and biomass of crop plants, as found in some recent studies [16,[38][39][40][41]. Although the mechanisms behind its effectiveness are still in need of investigation, it has been suggested that this stimulant effect on plant productivity may be due to the action of antioxidant molecules on cell division [16], in response to the activation of specific transcription genes, as previously observed by Tanase et al [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…However, the production of bamboo charcoal leads to a large amount of by-products, such as bamboo vinegar. Bamboo vinegar is an acidic, reddish brown, highly oxidized organic aqueous solution that is a smoke condensate during bamboo pyrolysis [9], which is rich in organic acids, phenols, alcohols, ketones, and other organic components. It is due to the thermal conversion of hemicellulose, cellulose, and lignin from bamboo.…”
Section: Introductionmentioning
confidence: 99%